Characterization of Yellow Rust (Puccinia striiformis) Resistance and Genetic Diversity in Nepalese Wheat Genotypes - Baidya, Suraj; Bhardwaj, Subash C.; Shrestha, Sundar M.; Mahto, Baidya N.; Manandhar, Hira K. (Journal of the Plant Protection Society, 2018)
Wheat (Triticum aestivum L.) is third important crop in Nepal after rice and maize. Yellow rust caused by Puccinia striiformis Westend. is a major disease of hills and adjoining foot hills. Both seedling and adult plant stage evaluations were carried out to characterize yellow rust resistance (Yr) genes in 105 Nepalese wheat genotypes at ICAR- Indian Wheat and Barley Research Institute, Regional Station, Shimla India. Eleven pathotypes of P. striiformis were used in seedling evaluation for identifying the resistance gene/s for yellow rust disease. Two most virulent and predominant pathotypes 78S84 and 46S119 were used to screen for adult plant resistance (APR). Four different resistance genes were inferred in tested material viz, YrA, Yr2, Yr9 and Yr27 by the seedling test. The postulated genes were observed either singly or in combination with other gene/s. The resistance genes YrA and Yr2 were detected alone whereas Yr27 was postulated in combination with Yr9. Among them, Yr9 was most dominant gene and was postulated in 48 genotypes either singly or in combination with Yr27. Twenty-one genotypes were found to confer low infection types (ITs) with hypersensitive and non-hypersensitive reaction against all the tested pathotypes. Twenty two of genotypes showed APR to both the pathotypes whereas 43 genotypes showed susceptibility to both pathotypes. In which 16 genotypes had susceptible response both seedling and Adult plant stage against both the pathotypes. Likewise, 53 genotypes had APR to one or other pathotype.